Estudio de factibilidad para la creación del medio digital Killa Radio TV – Guaranda 2023 - Tacuri Quille, Hendry Misael (2023)
In this degree project, a feasibility study was conducted for the creation of the digital media Killa Radio TV in Guaranda 2023, which aims to determine the feasibility of successfully establishing a media that offers a combination of online radio and television, offering variety and focused on the local community. The research began with the analysis of the most important digital media in the city, observing through the methodology the demand for digital content needed by users. Surveys were conducted to the target population, interviews to people relevant to the research and an observation sheet for a content analysis of the competition. With the results obtained from the research, interesting data was obtained where it is observed that there is a high level of interest from the population of Guaranda to the creation of a new digital media, so communication strategies were carried out. Keywords: Feasibility Study, Digital Media, Communication Strategies.